Understanding Parents’ Choices Behind Rising Enrollment Demand: The Roles of Service Quality, Trust, and Word of Mouth: Evidence from an Islamic Elementary School in Indonesia - Harti, Lita Edia (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives:This study examines how service quality and word of mouth affect parents’ school choice at SDIT Amal Mulia in Depok, with trust as an intervening variable. Background Problems: The intense competition in elementary school selection is highlighted by the case of SDIT Amal Mulia, where its Grade 1 quota filled in just 10 minutes, demonstrating the critical need to understand the key factors driving parental decision-making. Research Methods:The research used a census method, surveying all 76 Grade 1 parents. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. Finding/Results: Service quality strongly influences school choice, both directly and indirectly through trust.Trust significantly affects parents’ decisions.Word of mouth has no significant direct or indirect effect on the school choice decision. Conclusion: Service quality and trust play a more decisive role than word-of-mouth recommendations in influencing parents' choice of elementary school.